INTEGRATING KHILAFAH AND DEMOCRACY THROUGH PROPHETIC SOCIAL SCIENCE: TOWARD AN ETHICAL FRAMEWORK OF ISLAMIC GOVERNANCE - Novianta Budi Surana; Wijaya, Riko; Ibnu Azka; Haramain, Fathur Baldan (UIN Antasari Banjarmasin, 2025)
Khilafah and democracy are two opposing poles according to many researchers. This assessment is actually reductive, because reading the two terms from one side, namely both as systems and forms of government. Democracy, as a system of government, is highly context-dependent, manifesting in various forms such as liberal, direct, or participatory democracy in various societies. Defenders of the caliphate are mistaken in interpreting the word caliphate mentioned in the Qur'an. Meanwhile, the plaintiffs of the caliphate agree with the assumption of the defense group. As a result, the assumption that the caliphate is a system and form of government continues to roll until it covers the original meaning of the caliphate itself. This article will clear the term caliphate from the pile of political tendencies and then reveal its original meaning. For that, the author proposes two problem formulations. First, what is the true meaning of the caliphate ? Second, how to reconcile the caliphate in a political sense with democracy ? In order to dissect the two problem formulations, the author will adopt two analytical knives, namely the thematic interpretation method and Kuntowijoyo's Prophetic Social Science. Thematic interpretation will reveal the basic meaning of the caliphate, while Kuntowijoyo's prophetic social science will synthesize the caliphate and democracy. This research will produce two conclusions. First, the caliphate is not a system and form of state, but rather a divine character that embodies the will to imitate God and personal responsibility for that character. Second, the caliphate manifests itself as an idea and movement based on science, not just doctrine and belief.